1989
DOI: 10.1021/ac00176a004
|View full text |Cite
|
Sign up to set email alerts
|

Flow field flow fractionation in hollow cylindrical fibers

Abstract: problems. First, certain bonded phases change in nature as well as in the amount of stationary phase; both of these effects result in irreproducible separations. Second, the degradation products from the bonded phase can contaminate a fraction isolated during a separation; such adulteration is of special consideration in preparative chromatography.We have developed two new classes of bonded phases that result in significantly increased stability of HPLC column packings during use. The first class uses bifuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…Figure 1 shows a scanning electron microscopy (SEM) image of an asymmetric polysulphone membrane. Lee et al [8] and later J6nsson and Carlshaf [9] showed that porous hollow fibres can be used as membranes for flow FFE In previous work in our laboratory [10,11], we Table I. For each type at least three membranes were tested.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Figure 1 shows a scanning electron microscopy (SEM) image of an asymmetric polysulphone membrane. Lee et al [8] and later J6nsson and Carlshaf [9] showed that porous hollow fibres can be used as membranes for flow FFE In previous work in our laboratory [10,11], we Table I. For each type at least three membranes were tested.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…It was noted above that FFF optimally requires the field and/or field gradient to be uniform across the breadth of the channel, and that the channel also be of uniform thickness across its breadth. An exception to this arrangement of a thin channel of uniform thickness with a transverse field is the axisymmetrical symmetry of hollow fibre FFF, where a fraction of the fluid flows radially outward through the permeable fibre wall (Jönsson & Carlshaf 1989;Wijnhoven et al 1995;Reschiglian et al 2005). On the other hand, a tubular channel with transverse field is not a suitable design for FFF, as explained by Giddings (2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hollow-fiber flow field-flow fractionation (HF FlFFF), a variant of FlFFF techniques, was first described in a few papers on separation of spherical latex standard particles [13,14], and recently it has been gaining interest as an efficient separation technique for particles [15,16], proteins [17][18][19], and cells [20,21]. Unlike the conventional FlFFF channel system having a rectangular channel design, HF FlFFF is operated in a cylindrical channel utilizing a hollow-fiber membrane module which is very simple in assembly and disposable.…”
Section: Introductionmentioning
confidence: 99%